Behind the State: Domestic Mechanisms and Procedures for the Implementation of Human Rights Judgments and Decisions. (13th August 2020) - Murray, Rachel; De Vos, Christian
Abstract: It is the state to whom the supranational body directs its decision on a human rights violation, and it is the state who is found in violation and must provide the appropriate remedies. The state, however, is not a single entity: it is composed of the executive (and a web of different ministries and departments), the legislature, and the judiciary, including administrative bodies and tribunals. Depending on the type of reparations ordered, one, several, or all of these actors may be implicated. By tracking the mechanics of what happens in practical terms at the national level after decisions from UN treaty bodies and the regional human rights commissions and courts are adopted, findings from a three-year research project underscore that implementation is a multi-faceted process and whether implementation and ultimately compliance occurs can be explained, in part at least, by the regulatory, practical and technical processes in place to respond to those supranational decisions. By examining the role of these state actors and the procedures by which reparations are implemented and complied with at the national level, this article attempts to dissect the concept of 'political will'. We conclude by providing some further thoughts on how litigators, states and supranational bodies themselves can adjust their methods accordingly.